Handwashing among Schoolchildren in Jatinangor, West Java - Faye, Cheryl May Chong Sue; Chrysanti, Chrysanti; Gondodiputro, Sharon (Althea Medical Journal, 2016)
Background: Diarrhea and pneumonia accounts for an estimated 40% of all child deaths around the worldÂ each year. Handwashing with soap could protect about 1 out of every 3 young children who get sick withÂ diarrhea and almost 1 out of 6 young children with respiratory infections like pneumonia. Although peopleÂ around the world clean their hands with water, very few use soap to wash their hands. Washing hands withÂ soap removes germs much more effectively. This study was undertaken to determine the level of knowledgeÂ and practice regarding proper handwashing among elementary school children.Methods: A descriptive study was conducted from August to October 2014 in Jatinangor using primary dataÂ from respondents who are 5th graders from four schools. A total of 49 males and 50 females were chosenÂ using cluster random sampling. Schoolchildren who were present, able and well were given questionnairesÂ after written informed consent was obtained from the schoolchildren and their guardians. Then, respondentsÂ demonstrated hand-washing techniques which were evaluated using a checklist.Results: Overall, 52% of the schoolchildren had moderate level of hand washing knowledge and 66% hadÂ bad handwashing practices.Conclusions: Despite having a moderate level of handwashing knowledge, the majority still had poorÂ handwashing practices. Handwashing programs should be carried out extensively to improve knowledgeÂ and practice.[AMJ.2016;3(2):170â4]DOI:Â 10.15850/amj.v3n2.795